2022
DOI: 10.3897/jhr.91.82812
|View full text |Cite
|
Sign up to set email alerts
|

First records of adventive populations of the parasitoids Ganaspis brasiliensis and Leptopilina japonica in the United States

Abstract: We report the first known incidence of two parasitoid species of the invasive pest, Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), in the United States (US). The discovery of Ganaspis brasiliensis (Ihering) (Hymenoptera: Figitidae) and Leptopilina japonica (Novković & Kimura) (Hymenoptera: Figitidae) in northwestern Washington State (US) was made shortly after their discovery in nearby southwestern British Columbia (Canada), indicating that contiguous populations of these species are established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…In fact, inundative biological control is currently applied against D. suzukii in Europe, where Trichopria drosophilae (Hymenoptera: Diapriidae) is the most promising and commercially available biocontroler (Gonzalez-Cabrera et al, 2019; Rossi-Stacconi et al, 2018). In the United States, as a result of quarantine studies in Switzerland and California (US), and given the specificity shown by the Ganaspis brasiliensis (Hymenoptera: Figitidae) groups, a petition submitted to USDA-APHIS was approved for the release of G. brasiliensis G1 group (Beers et al, 2022). Trichopria anastrephae has been proposed in Brazil as useful in greenhouses (Vieira et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, inundative biological control is currently applied against D. suzukii in Europe, where Trichopria drosophilae (Hymenoptera: Diapriidae) is the most promising and commercially available biocontroler (Gonzalez-Cabrera et al, 2019; Rossi-Stacconi et al, 2018). In the United States, as a result of quarantine studies in Switzerland and California (US), and given the specificity shown by the Ganaspis brasiliensis (Hymenoptera: Figitidae) groups, a petition submitted to USDA-APHIS was approved for the release of G. brasiliensis G1 group (Beers et al, 2022). Trichopria anastrephae has been proposed in Brazil as useful in greenhouses (Vieira et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In its native distributional areas, L. japonica is one of most abundant potential parasitoids of D. suzukii ( Kimura & Novković, 2015 ; Puppato et al, 2020 ); its occurrence in Europe( Puppato et al, 2020 ) and North America ( Abram et al, 2020 ; Abram et al, 2022 ; Beers et al, 2022 ) was identified only recently. Previous laboratory experiments in the United States indicated that South Korean L. japonica strains attacked the North American strains of D. suzukii readily ( Daane et al, 2016 ), supporting at least in part the suitability of L. japonica as a biocontrol agent for D. suzukii .…”
Section: Discussionmentioning
confidence: 99%
“…The narrow host range of G. brasiliensis has led to its recent approval for field release in the United States of America (Beers et al 2022). Leptopilina japonica, however, has not yet been approved for release in the USA due to its broader host range.…”
Section: Discussionmentioning
confidence: 99%
“…Two parasitoid wasp species, Leptopilina japonica Novković & Kimura and Ganaspis brasiliensis Ihering (Hymenoptera: Figitidae), have been proposed as candidate classical biological control agents for the small fruit pest D. suzukii (Lee et al 2019). These parasitoids have recently been detected in North America, specifically in southwestern British Columbia (BC), Canada (Abram et al 2020) and northwestern Washington State, USA (Beers et al 2022). Leptopilina japonica has the broader host range of the two parasitoids and successfully parasitizes several drosophilid species in four genera in laboratory trials (Kimura and Novković 2015;Girod et al 2018b;Daane et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation